Booklet-Based Education in Diabetes Mellitus Patients: A Scoping Review - Saritessa, Nining; Ibrahim, Kusman; Haroen, Hartiah (Media Publikasi Cendekia Indonesia, 2025)
Diabetes mellitus (DM) is a significant global health issue requiring effective patient self-management to prevent severe complications like cardiovascular disease and organ damage. Health education is crucial for empowering patients, and booklets offer a cost-effective, accessible, and structured medium for delivering essential information. This scoping review investigated the use and impact of booklet-based education for DM patients. Following the Arksey and O'Malley framework, researchers searched CINAHL, PubMed, and Scopus databases for original English-language studies published between 2015 and 2024, using keywords related to diabetes, education, and booklets. From the search, 11 relevant articles were selected for analysis. The findings consistently showed that using booklets as an educational intervention effectively improved DM patients' knowledge, self-efficacy, and self-care behaviours. Key themes identified included the direct impact of booklets on knowledge enhancement, the benefit of combining theoretical information with practical application advice within the booklets, and the important role of family support in successful diabetes management, which can be facilitated by shared educational materials. The success of booklets is attributed to their structured format, ease of understanding, and continuous accessibility for patients. Factors influencing the effectiveness of this educational approach include patient literacy levels, the degree of family involvement, and the frequency of educational reinforcement. In conclusion, booklet-based education is a proven, effective strategy for improving self-management components in DM patients. The review highlights booklets as affordable and flexible tools, while also suggesting areas for future research, particularly concerning long-term clinical outcomes and the potential for integrating booklet content with modern digital health.